(untitled) (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.4116.76-93. The triple bottom line approach of sustainability provides a balance in meeting the demands of economic, environmental and social issues, necessary condition for sustainable development on competitive and dynamic markets, with environmental requirements. This article aims to present the main actions related to the development of a group of nine companies in order to make them able to implement the innovations needed to adapt them to the environmental requirements while maintaining their competitive performance; these companies integrate a pilot project whose purpose is to support the sustainable development of the Brazilian electromedical equipment industry. Here are described plans to develop the necessary competencies, contemplating the psychosocial aspects that have an impact on the organization performance and also involve the required innovations for the integration of the multiple goals of this project.